The Place of Bosu Ball in Thesis Studies in Turkey: The Field of Sports Sciences - Yusuf Arikan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: When the literature on Bosu exercise applications is examined, it is seen that Bosu exercise applications are used for balance development, strength and postural control development, and development of motor skills. In addition, the Bosu ball, which has a wide usage area, can be used not only by standing on it in a vertical position, but also by standing in a horizontal position. Reporting of the positive effects of Bosu exercises on sportive performance by many researchers has attracted the attention of trainers and athletes and has made it a frequently used material in training programs. Aim: The aim of this research is to determine for what purpose the Bosu ball, which has a global popularity, is a research topic in postgraduate theses published in the field of sports sciences in Turkey. Methods: This research was designed using the systematic review method. Between 11.03.2022 and 07.04.2022, a total of 9 theses were reached as a result of the search made by searching the keyword "Bosu" in Turkish-English language by filtering the word "Spor" on the database of the National Thesis Center. As a result of the first evaluation made within the framework of inclusion criteria, it was determined that 1 thesis was outside the field of sports sciences and this thesis was not included in the research within the scope of exclusion criteria. Within the scope of inclusion criteria, it was determined that there were 8 postgraduate theses and these theses were included in the research and the data of the research were obtained. Results: When the theses included in the study were examined in terms of their levels, it was determined that five theses were at the master's level and three theses were at the doctoral level. When the theses included in the research are examined in terms of the number of publications by years, it is seen that only studies on the relevant subject have been published in the last six years. As a result of the research, it was determined that Bosu exercise material, which is the subject of research in the field of Physical Education and Sports Sciences, has been researched specifically to increase balance performance. The effects on performance parameters such as body composition, aerobic capacity and agility were also investigated in some theses. In addition to these, there is also a study examining whether it has effects on body image, self-design and stress level. Conclusion: It has been deduced that Bosu exercise practices, which are the subject of research in postgraduate theses in the field of Physical Education and Sports Sciences, have a positive effect on body composition, sportive performance and psychological aspects.